2006
DOI: 10.1021/jm060190+
|View full text |Cite
|
Sign up to set email alerts
|

Novel Structural Features of CDK Inhibition Revealed by an ab Initio Computational Method Combined with Dynamic Simulations

Abstract: The rational development of specific inhibitors for the ∼500 protein kinases encoded in the human genome is impeded by poor understanding of the structural basis for the activity and selectivity of small molecules that compete for ATP binding. Combining classical dynamic simulations with a novel ab initio computational approach linear-scalable to molecular interactions involving thousands of atoms, we have investigated the binding of five distinct inhibitors to the cyclin-dependent kinase CDK2. We report here … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 72 publications
2
32
0
Order By: Relevance
“…It is obvious that the best scoring function is able to explain only about 70% of the data variability and that the available scoring functions are not capable of describing all the physics behind the inhibitor binding to CDK2. Many authors have analysed the nature of CDK2-inhibitor binding using various methods and concluded that the dispersion interactions (part of van der Waals interactions) is important for inhibitor binding [17,18,27,68] and may outweigh electrostatics [23]. Evidently, however, not only the dispersion but also the other terms should be properly covered.…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that the best scoring function is able to explain only about 70% of the data variability and that the available scoring functions are not capable of describing all the physics behind the inhibitor binding to CDK2. Many authors have analysed the nature of CDK2-inhibitor binding using various methods and concluded that the dispersion interactions (part of van der Waals interactions) is important for inhibitor binding [17,18,27,68] and may outweigh electrostatics [23]. Evidently, however, not only the dispersion but also the other terms should be properly covered.…”
Section: Discussionmentioning
confidence: 99%
“…Quantum mechanical / Poisson Boltzmann Approaches. One of the earliest applications in a biological context of the local orbital methods described in Section 1.2.3 was performed by Heady et al to compute the free energy of binding of five inhibitors to the cyclin-dependent kinase CDK2 [267]. The motivation for studying the target CDK2 is that it is over-expressed in cancer cells and may contribute to their unregulated growth [271].…”
Section: Medicinal Chemistrymentioning
confidence: 99%
“…24 Even though it is a new code, it is already being used in an increasing number of studies of nanostructures 25 and biomolecular systems. [26][27][28] An example of the linear-scaling behaviour of the code is provided in Figure 1 where the time to perform single-point energy calculations on protein fragments of increasing size is plotted as a function of the number of atoms. In these calculations a value of r K = 10.6 Å was used.…”
Section: B Electrostatic Embedding In the Onetep Programmentioning
confidence: 99%